Pengaruh Literasi Keuangan, Gaya Hidup, dan Perilaku Pembelian Impulsif Terhadap Penggunaan Shopee Paylater Pada Generasi Z di Banjarmasin - Kristin Mariyani; Muhammad Risanta (Komunitas Dosen Indonesia, 2025)
The use of Paylater is one of the popular fintech services today. one of the largest maketplace, Shopee targets the younger generation by providing flexible payment options through the Shopee PayLater service. This study aims to examine how financial literacy, lifestyle, and impulse buying behavior influence the decision to use Shopee Paylater for Generation Z in Banjarmasin. This research utilizes a quantitative approach. In this study, the population consists of all Generation Z in Banjarmasin. The sampling technique used is non-probability sampling with the Slovin formula, the sample size for this research is determined to be 250 respondents. The sample criteria in this study are Generation Z with the age of 18-29 years (in 2024) and active users or have used shopee pay later. Analysis used in this study is Structural Equation Model (SEM) analysis. SEM calculations in this research are performed using the Smart PLS 3 program. The research findings indicate that Financial Literacy, Lifestyle and impulsive buying have significant influence on purchasing decisions using Shopee Paylater.